Faculty development programs in dentistry: The need and the way forward!! - Ritu Jain; Anushi Mahajan; Dinesh Kumar Badyal (Wolters Kluwer Medknow Publications, 2021)
Oral health-care delivery in India is rapidly evolving given the increasing awareness about oral health among the public, advances in dental science and technology, and the demand for high-quality care. The dental workforce needs to be trained to develop the required skills and attitudes for delivering quality dental care. Modifications are required in the dental curriculum to accommodate the changing needs of the society. There is an urgent need to incorporate advances in educational methods and technology in dental teaching/learning to prepare future dental practitioners for real-world challenges. The conventional training of dental faculty in India does not involve any training in educational methods and techniques. Faculty development programs organized on a regular basis in the institutions can be very helpful in training the teachers in the latest and evidence-based teaching/learning methods. This article highlights the current status of faculty development initiatives for improving dental education and also makes suggestions to improve faculty training in Indian dental institutions for future.